The consumer in-store purchasing behavior associated with deal-proneness for a hypermarket retailer in Croatia - Anić, Ivan-Damir (Array, 2008)
Abstract: This paper examines the relationship between consumer purchase behavior and in-store promotion proneness across five promotion types. The model was tested with data collected from a consumer survey, carried out in the high/ low Croatian hypermarket setting. The data were analyzed using descriptive statistics and the one-way analysis of variance (ANOVA). In general, research results support the proposed framework. Higher consumer deal-proneness was associated with promotion planning (except for advertised brands and free samples), in-store promotion search and purchases of promoted items (except for special island displays). Contrary to expectations, action store loyalty was positively related to deal-proneness. The framework provided helps retailers predict consumer response to in-store promotion and their purchases depending on deal-proneness, as the starting point in designing promotion campaign and enhancing the store competitiveness